Active mesopelagic prokaryotes support high respiration in the subtropical northeast Atlantic Ocean - Arístegui, Javier; Duarte, Carlos M.; Gasol, Josep M.; Alonso-Sáez, Laura (Geophysical Research Letters, 2015)
Here we provide evidence, based on prokaryote metabolic proxies and direct estimates of oxygen consumption, that the mesopelagic prokaryote assemblage in the subtropical Northeast Atlantic is an active one. It supports a high respiration (0.22 ± 0.05 _mol O2 l_1 d_1, corresponding to 68 ± 8 mmol CO2 m_2 d_1), comparable to that of the epipelagic zone during the same period (64–97 mmol C m_2 d_1). Our findings suggest that mesopelagic prokaryotes in the NE subtropical Ocean, as well as in other eastern boundary regions, are important carbon sinks for organic matter advected from the highly productive coastal systems, and would play a key role in the global carbon cycle of the oceans. 4 1 4 2,491 Q1 SCIE